Pulmonary Amyloidosis: A Diagnostic Challenge - Alves, Ana (2015)
Amyloidosis is characterized by amyloid extracellular deposition in organs and tissues. Pulmonary involvement is a rare manifestation of the disease and it can be focal or as part of systemic amyloidosis. We report two cases. Case 1: 71 year-old female with bronchiectasis and Sjogren’s syndrome, who complained of anorexia, weight loss and a productive cough. The diagnostic study included a surgical lung biopsy and histological examination demonstrated pulmonary amyloidosis. Case 2: 83 year-old male patient, ex-smoker, asymptomatic,whose routine chest x-ray showed a nodular opacity in the right lung field. A transthoracic biopsy revealed an amyloid lung tumor. These cases illustrate a rare disease which in Case 1 also coexisted with Sjögren’s syndrome and bronchiectasis. The most important differential diagnosis is cancer and so a definitive diagnosis is essential, as amyloidosis is usually benign and indolent.